Pengaruh Self Efficacy Dan Locus Of Control Terhadap Kinerja Pegawai Dinas Pendidikan Dan Kebudayaan Kota Banda Aceh - Mimiasri Mimiasri; Winda Putri Diah Restya; Lailatul Husna (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
Goals of this study to examine and analyze the influence of self-efficacy and locus of control on the employee performance of Education Department and Culture of Banda Aceh. The population in this study were all employees who working at the Education Department and Culture of Banda Aceh. The research sample is 55 respondents. This research uses associative quantitative method. The data analysis used is multiple linear analysis regression formula. The result of the research is that self-efficacy has no a significant effect on employee performance at the Education Department and Culture of Banda Aceh. Locus of Control has a significant effect on employee performance at the Education Department and Culture of Banda Aceh. Self Efficacy has no effect partially but simultaneously and Locus of Control partially and simultaneously influence the employee performance at the Education Department and Culture of Banda Aceh